Fluorescent organic exudates of corals and algae in tropical reefs are compositionally distinct and increase with nutrient enrichment. Issue 4 (15th March 2018) - Quinlan, Zachary A.; Remple, Kristina; Fox, Michael D.; Silbiger, Nyssa J.; Oliver, Thomas A.; Putnam, Hollie M.; Wegley Kelly, Linda; Carlson, Craig A.; Donahue, Megan J.; Nelson, Craig E.
Abstract: Dissolved organic matter (DOM) composition influences microbial community metabolism and benthic primary producers are a source of DOM in coral reefs. As reef benthic communities change, in part due to nutrient pollution, understanding impacts on reef microbial processes requires knowledge of DOM sources and composition. We conducted a multi‐week mesocosm experiment dosing four coral reef benthic constituents with three levels of nitrate and phosphate to contrast exudate composition and quantify the effects of nutrient enrichment on exudate release. Moderate nutrient enrichment enhanced bulk dissolved organic carbon exudation by all producers. Corals exuded rapidly accumulating DOM with a markedly high concentration of aromatic amino acid‐like fluorescent DOM components that clearly distinguishes them from algal exudates, which were dominated by humic‐like fluorescent components and did not accumulate significantly. Our results indicate that corals and algae release DOM of different quality and the quantity of DOM release increases with inorganic nutrient availability.